2012
DOI: 10.1016/j.ophtha.2012.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Segment Biometry during Accommodation Imaged with Ultralong Scan Depth Optical Coherence Tomography

Abstract: Purpose To measure by ultra-long scan depth optical coherence tomography (UL-OCT) dimensional changes in the anterior segment of human eyes during accommodation. Design Evaluation of diagnostic test or technology. Participants Forty-one right eyes of healthy subjects with a mean age of 34 years (range, 22–41 years) and a mean refraction of −2.5±2.6 diopters (D) were imaged in two repeated measurements at minimal and maximal accommodation. Methods A specially adapted designed UL-OCT instrument was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
92
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(97 citation statements)
references
References 32 publications
4
92
1
Order By: Relevance
“…Optical Coherence Tomography (OCT) is a promising tool to image the anterior segment of the eye, due to its high-resolution, high-speed and non-contact nature [21][22][23][24][25] [38], and increased coherence length of swept sources [39,40]. Some of these techniques have been successfully used to quantify the 3-D geometry of the anterior segment of the eye [30,39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical Coherence Tomography (OCT) is a promising tool to image the anterior segment of the eye, due to its high-resolution, high-speed and non-contact nature [21][22][23][24][25] [38], and increased coherence length of swept sources [39,40]. Some of these techniques have been successfully used to quantify the 3-D geometry of the anterior segment of the eye [30,39].…”
Section: Introductionmentioning
confidence: 99%
“…Ortiz et al reported the first 3-D in vivo topography of the human crystalline lens [30]. Quantitative analysis (in most cases limited to axial biometry) has also been reported from 2-D cross-sections of the anterior segment of the accommodating human eye in vivo [19,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Using ultralong scan depth optical coherence tomography, Du et al (7) measured dimensional changes in the anterior segment of human eyes during accommodation. The relative change in the pupil diameter with a maximum accommodation effort of -5 D was 21.74%.…”
Section: Pupil Diametermentioning
confidence: 99%
“…Table 1 is a compilation of the results of all studies that evaluated at least one of these three eye metrics during accommodation. Studies assessing the changes in central ACD , mean ACA (16) , and PD (3,7,26,28,29) during accommodation concluded that these metrics decreased after increasing the stimulus vergence. Figure 1 The changes in the peripheral ACD and ACA at different meridians during accommodation have not been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation